TLR8 and complement C5 induce cytokine release and thrombin activation in human whole blood challenged with Gram‐positive bacteria. Issue 4 (21st February 2020) - Ehrnström, Birgitta; Kojen, June F.; Giambelluca, Miriam; Ryan, Liv; Moen, Siv H.; Hu, Zhenyi; Yin, Hang; Mollnes, Tom E.; Damås, Jan K.; Espevik, Terje; Stenvik, Jørgen
Abstract: We recently showed that TLR8 is critical for the detection of Gram‐positive bacteria by human monocytes. Here, we hypothesized that TLR8 and complement together regulate antibacterial responses in human blood. Anticoagulated blood was treated with selective inhibitors of TLR8 and/or complement C5, and then challenged with live Streptococcus agalactiae (Group B streptococcus, GBS), Staphylococcus aureus, or Escherichia coli . Cytokine production, plasma membrane permeability, bacterial survival, phagocytosis, and activation of coagulation was examined. GBS and S. aureus, but not E. coli, triggered TLR8‐dependent production of IL‐12p70, IL‐1β, TNF, and IL‐6 in fresh human whole blood. In purified polymorphonuclear neutrophils (PMN), GBS and S. aureus induced IL‐8 release in part via TLR8, whereas PMN plasma membrane leakage and extracellular DNA levels increased independently of TLR8. TLR8 was more important than C5 for bacteria‐induced production of IL‐12p70, IL‐1β, and TNF in blood, whereas IL‐8 release was more C5 dependent. Both TLR8 and C5 induced IL‐6 release and activation of prothrombin cleavage, and here their combined effects were additive. Blocking of C5 or C5aR1 attenuated phagocytosis and increased the extracellular growth of GBS in blood, whereas TLR8 inhibition neither reduced phagocytosis nor intracellular killing of GBS and S. aureus . In conclusion, TLR8 is more important than C5 for production of IL‐12p70, IL‐1β, and TNF upon GBS and S. aureus infection in blood, whereas C5 is central for IL‐8 release and phagocytosis. Both TLR8 and C5 mediate IL‐6 release and activation of coagulation during challenge with Gram‐positive bacteria in blood. Abstract : Characterizes the roles of TLR8 and complement C5 in antibacterial responses in human whole blood.